2011
DOI: 10.4049/jimmunol.1003377
|View full text |Cite
|
Sign up to set email alerts
|

CCL20/CCR6 Feedback Exaggerates Epidermal Growth Factor Receptor-Dependent MUC5AC Mucin Production in Human Airway Epithelial (NCI-H292) Cells

Abstract: Mucous hypersecretion is an important feature of obstructive airway diseases such as asthma, chronic obstructive pulmonary disease, and cystic fibrosis. Multiple stimuli induce mucin production via activation of an epidermal growth factor receptor (EGFR) cascade, but the mechanisms that exaggerate mucin production in obstructive airway diseases remain unknown. In this study, we show that binding of CCL20, a G protein-coupled receptor (GPCR) ligand that is upregulated in the airways of subjects with obstructive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 56 publications
1
37
1
Order By: Relevance
“…In addition, we demonstrated that ORMDL3 selectively regulates activation of the ER localized transcription factor ATF6α signaling branch, a pathway we have demonstrated in human lung epithelial cells is linked to SERCA-2b, which is implicated in airway remodeling in asthma (24). Finally, our studies demonstrate that ORMDL3 activates several metalloprotease, chemokine, and OAS-regulated genes, several of whom have also been implicated in the pathogenesis of asthma (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Overall, these studies provide evidence for a mechanism to link an ER localized protein such as ORMDL3 to the pathogenesis of asthma.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…In addition, we demonstrated that ORMDL3 selectively regulates activation of the ER localized transcription factor ATF6α signaling branch, a pathway we have demonstrated in human lung epithelial cells is linked to SERCA-2b, which is implicated in airway remodeling in asthma (24). Finally, our studies demonstrate that ORMDL3 activates several metalloprotease, chemokine, and OAS-regulated genes, several of whom have also been implicated in the pathogenesis of asthma (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Overall, these studies provide evidence for a mechanism to link an ER localized protein such as ORMDL3 to the pathogenesis of asthma.…”
Section: Discussionmentioning
confidence: 73%
“…Transfection of ORMDL3 into primary human lung bronchial epithelial cells induced increased expression of genes with potential importance to asthma including metalloproteases (MMP-9, ADAM-8) (7-11), CC chemokines (CCL-20) (12)(13)(14)(15), and CXC chemokines (IL-8, CXC-10) (16-21), suggesting potential downstream pathways from ORMDL3 pertinent to the pathogenesis of asthma. The importance of these ORMDL3-regulated genes to asthma is suggested from studies demonstrating increased expression of many of these mediators in the airways of human asthmatics (MMP-9, ADAM-8, CCL-20, CXCL-10, IL-8) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), induction of these mediators by allergen inhalation in asthmatics (MMP-9, CCL-20, CXCL-10) (7,12,19), and inhibition of asthma outcomes in mice deficient in these genes (MMP-9, ADAM-8, CXCL-10) (8,9,11,20,21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Signaling through EGFR involves dual oxidase 1 and the production of reactive oxygen species to activate TNF-alpha converting enzyme (TACE, ADAM17), which induces mucin production via a pathway involving increased TGF- shedding and EGFR phosphorylation (Shao & Nadel, 2005). Binding of CCL20 to CCR6 has been shown to exaggerate EGFR-dependent MUC5AC production by human airway epithelial cells (Kim, Lewis, & Nadel, 2011). EGFR activation also participates in CXCL8 (IL-8) production by bronchial epithelial cells (Richter et al, 2002).…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%